Type 1 diabetes: etiology, immunology, and therapeutic strategies - van Belle, Tom L; Coppieters, Ken T; von Herrath, Matthias G (Physiological reviews, 2011)
Type 1 diabetes (T1D) is a chronic autoimmune disease in which destruction or damaging of the beta-cells in the islets of Langerhans results in insulin deficiency and hyperglycemia. We only know for sure that autoimmunity is the predominant effector mechanism of T1D, but may not be its primary cause. T1D precipitates in genetically susceptible individuals, very likely as a result of an environmental trigger. Current genetic data point towards the following genes as susceptibility genes: HLA, insulin, PTPN22, IL2Ra, and CTLA4. Epidemiological and other studies suggest a triggering role for enteroviruses, while other microorganisms might provide protection. Efficacious prevention of T1D will require detection of the earliest events in the process. So far, autoantibodies are most widely used as serum biomarker, but T-cell readouts and metabolome studies might strengthen and bring forward diagnosis. Current preventive clinical trials mostly focus on environmental triggers. Therapeutic trials test the efficacy of antigen-specific and antigen-nonspecific immune interventions, but also include restoration of the affected beta-cell mass by islet transplantation, neogenesis and regeneration, and combinations thereof. In this comprehensive review, we explain the genetic, environmental, and immunological data underlying the prevention and intervention strategies to constrain T1D.